Trend Library Cafe Dalam Pengembangan Tradisi Intelektual Masyarakat Aceh - Afrina, Cut; Hak, Nurul; Putra, Rona (Institut Agama Islam Negeri (IAIN) Curup, 2024)
This study examines the trend of libraries in the development of the intellectual tradition of Muslim communities in Aceh. This study used qualitative descriptive research. Data collection techniques are carried out using interviews, documentation, and observation. The data obtained are analyzed using data reduction techniques, data presentation, and conclusions. The results of this study show that the trend of libraries in the development of intellectual traditions of Muslim communities in Aceh, among them first, the cafÃ© library is an alternative library that is in great demand by students, second, the library is crowded at the end of the lecture period, Third, the books that are requested by visitors are novels, and comics